Developing Australian undergraduate students' science communication skills through collaboratively created digital knowledge maps - Hanewald, R.; Ifenthaler, Dirk (2014)
This chapter describes the use of digital knowledge maps within a Science Communication course taught at an Australian University across a rural and a metropolitan campus-with the view of increasing learning outcomes in future years. It explores the impact and extent of the students' learning, especially their prior knowledge, their attitude about working collaboratively in small groups, their perspective on using technology rich learning in general and using digital knowledge map in particular. In this 2011 study, 93 science communication students participated out of a total enrolment of 118 undergraduates. The knowledge maps were constructed in small groups of three to four students to allow for discussion and refl ection. Topics for each map such as Time travel, Alzheimer's disease, Genetically modifi ed food, were chosen from the natural science, particularly biology, physics, chemistry and the earth sciences. Most students had little and some even no prior knowledge of knowledge mapping. Although taught by fi ve different tutors across two campuses, the differences in learning outcomes between the rural and metropolitan setting were negligible. More than half of the students indicated that digital knowledge mapping helped them think about their topic.